US cultural diplomacy in Portugal during the Cold War: the origins of the Fulbright program - Rodrigues, L. N. (Cultural diplomacy in the world since 1945: prestige, influence, cooperation, 2019)
This presentation deals with the cultural and educational relations between the United States and Portugal in the early Cold War. It is built upon the premise that also underlines this whole event that cultural policies, cultural relations between states are a fundamental part of international relations. History of International Relations or International History has long been able to perform this “cultural turn”, overcoming an analysis based only on the more traditional fields of diplomatic, political, military or economic relations, to address what we call as ‘cultural diplomacy’.